Radicalization and counter-radicalization - Silva, Derek M. D.; Deflem, Mathieu (Sociology of crime, law, and deviance, 2020)
The fifteen chapters in this volume of Sociology of Crime, Law, and Deviance discuss a number of issues researchers in the fields of sociology, criminology, and criminal justice theorize, conceptualize, and measure racialization and counter-radicalization.